The Effect of Burnout on the Performance of Nurses at Aliyah I Hospital in Kendari City in 2023 - Muhammad Al Rajab,; Fajar Kurniawan ,; Marheni Fadillah Harun , (International Journal Of Health Science, 2023)
Performance is the work of an employee qualitatively and quantitatively in carrying out his duties in accordance with the obligations imposed on him. The purpose of this study was to see how burnout affects the performance of employees at RSU Aliyah I Kendari City in 2023. Using complete sampling, the population consists of 42 permanent nurses. Data collection methods include observation, interviews, and distributing questionnaires. Chisquare is the analytical approach used. Based on the research findings, 11 (68.3%) of the 16 respondents who experienced burnout in the low group performed well in the good category. Furthermore, 17 (65.4%) of the 26 respondents in the high burnout category were satisfied with patient satisfaction. On the other hand, the value of ρ<1. We get α = 0.031 < 0.05 and Ho is discarded. Therefore, at Aliyah I General Hospital in Kendari City in 2023, burnout can be interpreted as affecting nurse performance. Efforts to improve performance must pay attention to the comfort of nurses' work, need to pay attention to the skills and workload of nurses, and foster a sense of responsibility.